HUBUNGAN POLA MAKAN DAN STATUS GIZI TERHADAP KEJADIAN STUNTING PADA BADUTA USIA 6-23 BULAN DI KECAMATAN POLONGBANGKENG UTARA TAHUN 2019: HUBUNGAN POLA MAKAN DAN STATUS GIZI TERHADAP KEJADIAN STUNTING PADA BADUTA USIA 6-23 BULAN DI KECAMATAN POLONGBANGKENG UTARA TAHUN 2019 - Umi Kalsum; Veni Hadju; Suryani As’ad (Poltekkes Kemenkes Bandung, 2020)
Nutrition problems are the main cause of the burden of disease in children globally. The occurrence of a short toddler or stunting is one of the nutritional problems experienced by toddlers in the world today. Relationship of Eating Pattern and Nutrition Status with Stunting Occurrence in The Toddler Anging 6-23 Months in North Polongbangkeng Distric. This study aims to determine the risk factors for stunting in the toddler aging 6-25 months after controlling for other variables in North Polongbangkeng Dsitrict, in 2019. This type of research is obsevasional analytic with case control desing. The number of research samples as many as 68 cases, namely toddler suffering from stunting and 68 people as controls, namely normal / not stunting toddlers. Bivariate data nalysis used chi-square test with α=0.05 and multivariat analysis used logistic regression test.The result showd that a significant risk factor for the occurrence of stunting, namely maternal factors which included a history of eating patterns and nutritional status based on anemia and KEK. History for eating patterns p=0,000 (<0,05) with an OR value of 7,824 times having stunting. Nutritional status based on anemia was p=0,026 (<0,05) with an OR value of 2.473 times the risk of stunting. Nutritional status based on KEK is p=0,000 (<0,05) with OR = 5,093 times the risk of stunting. There is a relationship between diet and maternal nutritional status on the risk of stunting in baduta.